2022
DOI: 10.3390/ph15080914
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene Receptor Antagonist, Montelukast Ameliorates L-NAME-Induced Pre-eclampsia in Rats through Suppressing the IL-6/Jak2/STAT3 Signaling Pathway

Abstract: Aims: To investigate the potential protective role of montelukast (Mont) in the pre-eclampsia rat model induced by L-NG-Nitro arginine methyl ester (L-NAME). Methods and materials: Thirty-two pregnant female albino Wistar rats were assigned to four groups: the control group: pregnant rats received vehicles; the Mont group: pregnant rats received Mont (10 mg/kg/day, p.o.) from the 6th to the 18th day of gestation; the L-NAME group: pregnant rats received L-NAME (50 mg/kg/day, i.p.) from the 9th to the 18th day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…According to previous studies, FOXO3 depletion leads to reduced migration and invasion of trophoblast cells, arrested cell cycle in G1 phase, and increased apoptosis under oxidative stress 37 . JAK/STAT3 pathway is indispensable for the regulation of the invasion of trophoblast and spiral artery remodeling, significant histopathological alterations in the placenta 38 . Elevated levels of soluble AXL indicate placental endothelial dysfunction by regulating critical angiogenic molecules 39 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…According to previous studies, FOXO3 depletion leads to reduced migration and invasion of trophoblast cells, arrested cell cycle in G1 phase, and increased apoptosis under oxidative stress 37 . JAK/STAT3 pathway is indispensable for the regulation of the invasion of trophoblast and spiral artery remodeling, significant histopathological alterations in the placenta 38 . Elevated levels of soluble AXL indicate placental endothelial dysfunction by regulating critical angiogenic molecules 39 .…”
Section: Discussionmentioning
confidence: 96%
“…37 JAK/STAT3 pathway is indispensable for the regulation of the invasion of trophoblast and spiral artery remodeling, significant histopathological alterations in the placenta. 38 Elevated levels of soluble AXL indicate placental endothelial dysfunction by regulating critical angiogenic molecules. 39 BCL2L1 can be inhibited by let-7a in trophoblasts, leading to early-onset severe PE.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of WBC function during pregnancy was related to the inhibition of humoral-cellular immune regulation function. Due to the poor ability of N denaturation, WBC is detained in the capillary in the low perfusion area of the thrombosis site, which releases lysosomes, histamines, leukotrienes, and other substances that are harmful to blood flow, resulting in microcirculation blood flow disorder ( Moodley et al, 2020 ; Abdelzaher et al, 2022 ). The etiology theory of hypertensive disorder complicating pregnancy also believes that the abnormal immune regulation function and the toxic effect of oxidative stress reaction ultimately lead to N inflammatory infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that they all had good binding with RSV except STAT3. However, a recent study has demonstrated that the IL6/Jak2/STAT3 signaling pathway is involved in the development of PE ( 63 ). These results finally indicated that these six targets might be the targets of RSV against PE, and more experimental and clinical studies are still needed in the future.…”
Section: Discussionmentioning
confidence: 99%